Multiple yield traits for selection of mulberry (Morus spp) germplasm for higher productivity - BANERJEE, R; CHOWDHURI, S ROY; SAU, H; DAS, B K; GHOSH, P L; SARKAR, A (The Indian Journal of Agricultural Sciences, 2011)
A field expseriment was conducted during 2001–05 to evaluate 24 mulberry (Morus spp) germplasm accessions and 1 check cultivar for yield and its attributes. Significant variation for all the traits, namely total shoot length, shoots/plant, longest shoot length, single leaf weight, leaf area and leaf yield/plant indicates the presence of variability. Moreover high heritability along with high genetic gain as a percentage of mean for all the traits indicated improvement of these traits through selection. Similarity in response with the check cultivar for total shoot length, shoots/plant and longest shoot length was exhibited by ‘MI 0290’ and ‘MI 0313’ and resulted as 880.8 cm, 9.3 and 116.1 cm in ‘MI 0290’ and 855.5 cm, 8.8 and 119.3cm in ‘MI 0313’ respectively. These genotypes may have the potentials for exploitation in future mulberry improvement programme. Ranking on the basis of scoring of each genotype separately for individual trait showed that the check cultivar was the top scorer. Accessions statistically identical to the check for total shoot length, longest shoot length, single leaf weight and single leaf area were ranked high. Besides ‘MI 0310’ scored well in ranking and statistically at par to check in single leaf weight (3.7 g), leaf area (183.9 cm2) and leaf yield (592.2 g). Therefore ‘MI 0310’ may be utilized as a source material for simultaneous improvement of many important traits towards development of mulberry with higher productivity. Being triploid, the check cultivar can not be used as a breeding material